Marker Based Standardisation of Saptang Guggul Using HPTLC Validated Method for Guggulsterone, Gingerol, Gallic Acid, Piperine Quantification - Mr. Rohan Chandrasen Dongare; Dr. Atul N Chandu; Dr. Sujit Nagare (The Bioscan, 2025)
For the purpose of standardizing Saptang Guggul, a straightforward, accurate, and precise High-Performance Thin-Layer Chromatography (HPTLC) method was created and approved, a classical Ayurvedic polyherbal formulation. The method involved estimation of [insert key marker compounds, e.g., guggulsterone, gallic acid, etc.] using a suitable mobile phase and detection wavelength. Validation was done in compliance with ICH rules, assessing linearity, accuracy, precision, specificity, & robustness. The developed method provides an effective tool for quality control and standardization of Saptang Guggul. KEYWORDS Saptang Guggul, HPTLC, Standardization, Validation, Polyherbal formulation, ICH guidelines